Rationality and Non-Rationality Testing to Different Form of Whistleblowing - Andi Ina Yustina; Phyrel Asri Sugiyanto; Christine Novita Dewi; Hadi Mahmudah (Asia Pacific Fraud Journal, 2022)
Whistleblowing is an incredibly effective method of preventing and identifying fraud. Indeed, a variety of circumstances contribute to an employee’s choice to file a whistle-blower complaint. The goal of this research is to illustrate the effect of perceived danger severity and perceived wrongdoing severity on whistleblowing intention using emotion as a moderator. This research used a quantitative approach. The major source of data was questionnaires issued to workers at a variety of businesses. A total of 207 samples were taken. In our investigation, we used SEM-PLS. Threat perception has an impact on negative mood and has a detrimental effect on whistleblowing intention, according to the research. Whereas the perceived gravity of misbehaviour improves one’s mood and raises the possibility of whistleblowing.